COMENTARIO PERDIDO A PETRONIO - Moya del Baño, Francisca; Fortuny Previ, Filomena (Myrtia, 1990)
A series of letters written by D. Juan de Fonseca y Figueroa (1578-1627), to be found in the manuscript 'Madrid, Biblioteca Nacional' 12639, provide information about the existence of a Commentary to Petronius. The nature of this work may be deducted from the above letters.